Relationship Between Anxiety Levels In Pregnant Women And Length Of Second Stage Labor At Bara-Baraya Public Health Center, Makassar In 2024 - Fahad Ahmad Hudzaif Ridwan; Anna Sari Dewi; Nur Fadhillah Khalid; Muh. Alim Jaya; Mona Nulanda (Sean Institute, 2025)
Anxiety during pregnancy and labor is one of the psychological factors that can affect the labor process , including the duration of labor in Stage II. High anxiety can lead to ineffective uterine contractions , thus prolonging the duration of labor . This study aims to determine the relationship between the level of anxiety in pregnancy women with the duration of labor during stage II at the Bara- Baraya Makassar Health Center in 2024. This study used an observational analytics design with a cross-sectional approach . The research sample was pregnant women who underwent normal labor at the Bara- Baraya Health Center, which was selected using purposive sampling technique . Measurements of anxiety level was carried out with the DASS-42 questionnaire , while data on the duration of labor at stage II was obtained from the patient's medical record . Data analysis was performed using the Likelihood Ratio statistical test . Data analysis showed a relationship between the anxiety level​ pregnant women and the duration of labor in Stage II. Mothers with a higher level of anxiety trend to experience longer​ second stage of labor than mother with a lower level of anxiety . Anxiety in pregnant women affects the duration of labor in Stage II. Therefore , effective interventions are needed in the psychological management of pregnant women to reduce anxiety and facilitate the labor process.